Porous ceramic, preparation method thereof, atomizing core and electronic atomizing device

By adding expandable graphite and high thermal conductivity materials to porous ceramic raw materials, the problems of deformation and oil leakage of porous ceramic atomizing cores during sintering are solved, improving thermal conductivity and atomization efficiency, and enhancing user experience.

CN119285370APending Publication Date: 2025-01-10品度生物科技(深圳)有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411387763.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-07
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Porous ceramic atomizing cores are prone to deformation during sintering, resulting in low production efficiency and the risk of oil leakage. Furthermore, their low thermal conductivity leads to insufficient preheating of the high-viscosity aerosol generation matrix, resulting in insufficient oil supply and affecting the taste experience.

Method used

Porous ceramic raw materials containing expandable graphite are used, and fine flake graphite is prepared by intercalation modification. The expansion property of graphite during high-temperature sintering is used to resist the shrinkage of the ceramic matrix and to fit tightly with the oil guide tube. At the same time, high thermal conductivity materials such as silicon nitride and aluminum nitride are added to improve thermal conductivity.

Benefits of technology

It improves the structural stability and thermal conductivity of the porous ceramic atomizing core, solves the oil leakage problem, and enhances the preheating effect of the high-viscosity aerosol generation matrix, thereby improving atomization efficiency and user taste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285370A_ABST
    Figure CN119285370A_ABST
Patent Text Reader

Abstract

The invention discloses porous ceramic and a preparation method thereof, an atomization core and an electronic atomization device, the porous ceramic is prepared from ceramic raw materials, the ceramic raw materials comprise inorganic powder and organic components, and the inorganic powder comprises, by weight, 35-80 parts of ceramic aggregate, 5-30 parts of a binder, 5-20 parts of a pore forming agent, 3-15 parts of a sintering aid and 3-12 parts of expandable graphite. By adding the expansible graphite, the volume of the expansible graphite can be rapidly expanded in the high-temperature sintering process, shrinkage of the ceramic matrix can be resisted, integrated sintering preparation of the porous ceramic body and the oil guide pipe is promoted, and a sintered finished product has reliable structural stability and high production efficiency; in addition, the porous ceramic atomizing core has certain heat conduction performance, and the problems that a high-viscosity aerosol generating matrix cannot be fully preheated, the oil conduction rate of the high-viscosity aerosol generating matrix in the ceramic atomizing core is low, oil supply is insufficient during suction and the like can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of porous ceramics, and in particular to a porous ceramic and a preparation method thereof, an atomization core, and an electronic atomization device. Background Art

[0002] With the development of the electronic atomizer industry, atomization technology and atomization materials are also constantly updated and iterated. The electronic atomizer includes an atomization core. Porous ceramics are a form of embodiment of the atomization core. The atomization core is provided with a heating component on the porous ceramic. The liquid matrix is ​​absorbed and stored by the liquid conductivity and liquid storage performance of the porous ceramic, and the liquid matrix absorbed in the porous ceramic is heated by the heating component, thereby atomizing to form an aerosol. However, porous ceramics will inevitably shrink during the debinding and sintering process. The sintering shrinkage rate of porous ceramics is often greater than 5%. The large shrinkage rate will cause deformation and other problems during ceramic sintering. And the ceramic atomization core assembly after sintering usually needs to be wrapped with a layer of oil-conducting cotton around it, and then the ceramic atomization core is assembled into the oil guide tube. In this case, the production efficiency is low, and due to the poor consistency of the cotton and the poor stability of the cotton-wrapping process, there is a risk of oil leakage during use, which leads to unstable atomization quality and easy leakage of the assembled electronic cigarette, and low production efficiency.

[0003] In addition, the high-viscosity aerosol-generating matrix cannot be fully preheated due to the low thermal conductivity of the current ceramic atomizer core, resulting in a low oil conduction rate in the ceramic atomizer core and insufficient oil supply during inhalation, which leads to a poor taste experience. Summary of the invention

[0004] The purpose of the present invention is to provide a porous ceramic and a preparation method thereof, an atomization core, and an electronic atomization device to solve the problems mentioned in the above background technology.

[0005] The present invention provides a porous ceramic, which is made of ceramic raw materials, wherein the ceramic raw materials include inorganic powder and organic components, wherein the inorganic powder includes, by weight, 35-80 parts of ceramic aggregate, 5-30 parts of binder, 5-20 parts of pore former, 3-15 parts of sintering aid and 3-12 parts of expandable graphite;

[0006] The organic components include 15-35 parts of plasticizer and 1-10 parts of surfactant by weight.

[0007] In some embodiments, the ceramic aggregate includes 5-20 parts of a first base material, 15-60 parts of a second base material, and 5-35 parts of a third base material;

[0008] The first base material includes one or two of diatomaceous earth and attapulgite;

[0009] The second base material includes one or both of silicon nitride and aluminum nitride;

[0010] The third base material includes mullite powder.

[0011] In some embodiments, the sintering aid is one or both of wollastonite and diopside.

[0012] In some embodiments, the pore-forming agent includes one or more of sucrose, polystyrene microspheres, wood powder, phenolic resin powder, epoxy resin powder, and starch;

[0013] and / or, the plasticizer comprises paraffin;

[0014] And / or, the surfactant includes one or both of beeswax and stearic acid.

[0015] In some embodiments, the inorganic powder comprises, by weight, 5-15 parts of the first base material, 20-50 parts of the second base material, 10-30 parts of the third base material, 10-20 parts of the binder, 5-15 parts of the pore former, 5-10 parts of the sintering aid, and 5-10 parts of the expandable graphite, and the weight ratio of the inorganic powder to the organic component is 100:28-100:38.

[0016] The present invention also provides a method for preparing a porous ceramic, the method comprising the following steps:

[0017] S1. Ingredients: According to the formula, ceramic aggregate, binder, pore former, sintering aid, expandable graphite, plasticizer and surfactant are weighed to obtain an inorganic powder mixture and an organic component mixture respectively;

[0018] S2, mixing and drying: mixing the inorganic powder mixture in step S1 uniformly and drying to remove moisture;

[0019] S3, preparing wax slurry: heating and melting the organic component mixture in step S1, and then adding the inorganic powder mixture in step S2 and stirring evenly to obtain wax slurry;

[0020] S4, die-casting: placing the wax slurry in step S3 into a mold containing an oil guide tube and a heating component for die-casting, so that the porous ceramic blank, the oil guide tube and the heating component are integrally formed, and the inner side wall and the outer peripheral side of the porous ceramic blank are respectively in contact with the heating component and the oil guide tube;

[0021] S5, dewaxing and sintering: Dewaxing and sintering the porous ceramic body in step S4 to obtain a porous ceramic atomizing core.

[0022] In some embodiments, step S5 of dewaxing and sintering comprises:

[0023] S50, pre-sintering the body: placing the porous ceramic body in an air furnace for pre-sintering to remove wax from the porous ceramic body;

[0024] S51, sintering the porous ceramic atomizer core: placing the pre-fired porous ceramic body in a vacuum sintering furnace for sintering to obtain a porous ceramic atomizer core.

[0025] In some embodiments, before the step S1 batching, the process further includes preparing the expandable graphite:

[0026] Take graphite, use a strong oxidant to perform intercalation modification under strong acid conditions, wash with water until the pH value is weak acid, and bake and dry to obtain expandable graphite.

[0027] The present invention also provides a porous ceramic atomizing core, wherein the porous ceramic has a porosity of 50-60%, a shrinkage of -0.10-0.05%, and a thermal conductivity of 2.0 W / (m·K)%-3.0 W / (m·K).

[0028] The present invention also provides an electronic atomization device, comprising the above-mentioned porous ceramic atomization core.

[0029] Compared with the prior art, the present invention has the following beneficial effects: a porous ceramic provided by the present invention has expandable graphite added to the ceramic raw material. The expandable graphite is used as a filler and is prepared by intercalation modification of fine flake graphite. Its volume can be rapidly expanded during the high-position sintering process, and the shrinkage of the ceramic matrix can be resisted. The porous ceramic green body, the oil guide tube and the heating component can be sintered and prepared as a whole. The sintered porous ceramic atomization core has reliable structural stability, and it is easy to solve the problems of the existing ceramic atomization core being troublesome to assemble and easy to leak oil. In addition, the porous ceramic atomization core of the present invention has certain thermal conductivity, and can solve the problems that the high-viscosity aerosol generation matrix cannot be fully preheated, the oil conduction rate in the ceramic atomization core is low, and insufficient oil supply occurs during suction. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Schematic diagram of the effect of expansion temperature on the expansion volume of expandable graphite in an embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with the specific embodiments. Preferred embodiments of the present invention are provided in the specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0033] Unless otherwise specified or there is a contradiction, the terms or phrases used in this invention have the following meanings:

[0034] In the present invention, "one or more" refers to any one, any two or more of the listed items. Among them, "multiple" refers to any two or more of the listed items.

[0035] When a numerical range is disclosed in the present invention, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise indicated, all ranges disclosed in the present invention should be understood to include any and all subranges included therein.

[0036] In the present invention, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0037] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0038] In one embodiment, a porous ceramic is made of ceramic raw materials, the ceramic raw materials include inorganic powder and organic components, and the weight ratio of the inorganic powder to the organic component is 100:16-100:45.

[0039] The inorganic powder includes 35-80 parts of ceramic aggregate, 5-30 parts of binder, 5-20 parts of pore former, 3-15 parts of sintering aid and 3-12 parts of expandable graphite. The organic component includes 15-35 parts of plasticizer and 1-10 parts of surfactant.

[0040] In some embodiments, the ceramic aggregate includes 5-20 parts of the first base material, 15-60 parts of the second base material, and 5-35 parts of the third base material.

[0041] The first base material includes diatomaceous earth, one or two of attapulgite. The main chemical component of diatomaceous earth is silicon dioxide, which is a porous material with low density and large specific surface area. The main chemical component of attapulgite is hydrated magnesium aluminum silicate, which is a material with a three-dimensional spatial chain structure and a special needle and rod-shaped crystal structure, and has strong adsorption properties. Diatomaceous earth and one or two of attapulgite are added to the ceramic raw materials as aggregates to improve the adsorption properties of porous ceramics, while also improving the liquid locking ability of the porous ceramic atomization core and reducing the risk of leakage.

[0042] The second base material includes one or two of silicon nitride and aluminum nitride. Compared with silicon dioxide, silicon nitride and aluminum nitride have the characteristics of high thermal conductivity and high strength. Selecting a reasonable amount can improve the thermal conductivity of the porous ceramic atomizer core, and can solve the problems that the high-viscosity aerosol generation matrix cannot be fully preheated, the oil conduction rate in the ceramic atomizer core is low, and the oil supply is insufficient during suction.

[0043] The third base material includes mullite powder, which provides a higher strength of the skeleton after sintering and improves the thermal conductivity to a certain extent.

[0044] In some embodiments, the sintering aid is one or both of wollastonite and diopside. Wollastonite and diopside reduce the sintering temperature of the green body during the sintering process and both do not contain organic matter and structural water. The drying and sintering shrinkage is very small, which can reduce the overall sintering shrinkage of the ceramic to a certain extent. In the preparation of raw materials, the mass fraction of the sintering aid is 3 to 15 parts. For example, the mass fraction of the sintering aid can be, but is not limited to, 3 parts, 5 parts, 8 parts, 12 parts, 15 parts, or a range consisting of any two of these values.

[0045] In some embodiments, expandable graphite is used as a filler, which is a material with a layered structure, prepared by intercalation modification of fine flake graphite, and its volume can be rapidly expanded during high-temperature sintering, which can resist the shrinkage of the ceramic matrix, and can promote the close fit of porous ceramics and oil guide tubes. Preferably, when preparing the raw materials, the mass fraction of expandable graphite is 3-12 parts. If the content of expanded graphite is too high, the ceramic matrix expands too much, which easily leads to defects such as microcracks in the matrix and excessive porosity, and the matrix reliability is poor. In addition, the porosity is too high, and the oil conduction is too fast, which is not conducive to the restoration of the atomized liquid atomization mouthfeel, affecting the user's suction experience. If the content of expanded graphite is too low, the expansion effect is not obvious, and the volume shrinkage during the high-temperature sintering of porous ceramics cannot be offset.

[0046] In a more preferred embodiment, the inorganic powder comprises, by weight, 5-15 parts of the first base material, 20-50 parts of the second base material, 10-30 parts of the third base material, 10-20 parts of a binder, 5-10 parts of a sintering aid, 5-15 parts of a pore former, 5-10 parts of a sintering aid, and 5-10 parts of expandable graphite.

[0047] The organic component includes 15-35 parts of plasticizer and 1-10 parts of surfactant by weight; for example, the weight of the plasticizer can be but is not limited to 15 parts, 16 parts, 18 parts, 20 parts, 23 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts or a range consisting of any two of these values; optionally, in the ceramic raw material, the weight of the plasticizer is 15-23 parts;

[0048] The weight ratio of the inorganic powder to the organic component is 100:28-100:38; for example, the weight ratio of the inorganic powder to the organic component can be, but is not limited to, 100:28, 100:30, 100:32, 100:35, 100:36, 100:37, 100:38 or a range consisting of any two of these values. Optionally, in the ceramic raw material, the weight ratio of the inorganic powder to the organic component is 100:30-100:35.

[0049] In one embodiment of the present invention, the pore-forming agent includes one or more of sucrose, polystyrene microspheres, wood powder, phenolic resin powder, epoxy resin powder, and starch. It is understandable that the pore-forming agent is not limited thereto, and can also be other pore-forming agents commonly used in the art. Adding the pore-forming agent to the ceramic raw material can form a uniform porous structure, and the porosity of the porous ceramic atomization core can be controlled within a reasonable range by controlling the amount of the pore-forming agent.

[0050] In one embodiment of the present invention, the plasticizer includes paraffin wax; the combination of paraffin wax and surfactant can improve the compatibility of organic components, making it easier to mix the raw materials evenly and making the porous ceramic body more plastic.

[0051] In one embodiment of the present invention, the surfactant includes one or both of beeswax and stearic acid. Beeswax, as a surfactant, can improve the molding and demoulding properties of ceramic raw materials. Beeswax has a high melting point and a large molecular weight, and is very easy to form a network. Adding a certain amount of beeswax to the ceramic raw material can form a network structure in the organic component, and the ceramic raw material powder is network-coated.

[0052] Due to its small molecular weight and strong modification, stearic acid can reduce the interfacial energy between inorganic powder and plasticizer paraffin, improve the wettability between the two, and at the same time act as a bridge between the plasticizer and ceramic raw material powder particles, promoting the bonding between the ceramic raw material powder particles and the plasticizer.

[0053] The present invention also provides a method for preparing a porous ceramic, the preparation method comprising the following steps:

[0054] S1. Ingredients: According to the formula, ceramic aggregate, binder, pore former, sintering aid, expandable graphite, plasticizer and surfactant are weighed to obtain an inorganic powder mixture and an organic component mixture respectively;

[0055] S2, mixing and drying: mixing the inorganic powder mixture of step S1 evenly and drying to remove moisture;

[0056] S3, preparing wax slurry: heating and melting the organic component mixture of step S1, and then adding the inorganic powder mixture of step S2 and stirring evenly to obtain wax slurry;

[0057] S4, die casting: placing the wax slurry in step S3 into a mold containing an oil guide tube and a heating component for die casting, so that the porous ceramic body, the oil guide tube and the heating component are integrally formed, and the inner side wall and the outer peripheral side of the porous ceramic body are respectively in contact with the heating component and the oil guide tube;

[0058] S5, dewaxing and sintering: Dewaxing and sintering the porous ceramic body in step S4 to obtain a porous ceramic atomizing core.

[0059] Among them, the heating component is a tubular structure formed by winding a heating mesh sheet with a mesh structure. The oil guide tube can be an oil guide tube with a plurality of oil guide holes on the side wall, and the oil guide tube can be made of ceramic or metal tubes. During sintering, the wax slurry is poured into the gap formed by the oil guide tube and the heating component, that is, the ceramic blank, the oil guide tube, and the heating component are sintered and formed as a whole. Since expandable graphite is added to the ceramic raw material, the shrinkage rate of the ceramic sintering process can be resisted, so that the inner and outer side walls of the ceramic can be closely attached to the heating component and the outer oil guide tube, thereby improving the production efficiency and product stability of the atomizer core.

[0060] In one embodiment, the method for preparing expandable graphite is as follows:

[0061] Add graphite to the strong acid solution and stir continuously until the mixture is evenly mixed to form a uniform suspension;

[0062] A strong oxidant was added in batches several times with intermittent stirring to acidify and intercalate the fine flake graphite. The reaction time was 90 min and the reaction temperature was 40°C.

[0063] After the reaction is completed, the reaction product is washed with water until it is neutral, and then placed in an oven at 60° C. and dried for 12 h to obtain expandable graphite.

[0064] The graphite is flaky graphite with a particle size of 500 to 5000 meshes. The strong acid solution includes one or more of concentrated sulfuric acid, concentrated nitric acid, perchloric acid and the like. The strong oxidant includes one or more of potassium permanganate, hydrogen peroxide, ammonium persulfate, sodium chlorate and potassium perchlorate. The pH value after washing with water is 5 to 7.

[0065] Preferably, the strong acid solution is 85% sulfuric acid and the strong oxidant is potassium permanganate. Graphite is a crystal with a layered structure, which has the characteristics of weak interlayer bonding and large interlayer spacing. In this crystal, each layer is a macromolecule formed by δ bonds and π bonds, and the layers are bonded by very weak van der Waals forces, with an interlayer spacing of about When potassium permanganate is present, the edges of flake graphite are activated and the stability of its interlayers is destroyed. Relatively speaking, sulfate ions can be intercalated between graphite layers and combined with the hexagonal mesh plane of carbon to form graphite hydrogen sulfate (GIC). At this time, the distance between graphite layers can be expanded to The graphite salt is unstable. The sulfate in the expandable graphite decomposes at high temperature to produce gas, which overflows from the interlayer and generates a huge driving force. This driving force overcomes the van der Waals force between the graphite layers, increases the interlayer spacing, and rapidly expands the volume of the graphite.

[0066] Specifically, step S5 of dewaxing and sintering includes:

[0067] S50, pre-sintering of the body: placing the porous ceramic body in an air furnace for pre-sintering to remove the wax in the porous ceramic body, the pre-sintering temperature is 200°C, and the heat preservation time is 3h;

[0068] S51. Sintering of porous ceramic atomization core: placing the pre-fired porous ceramic blank in a vacuum sintering furnace for sintering to obtain a porous ceramic atomization core. The sintering conditions are vacuum degree below 0.01 Pa, sintering temperature of 700-900° C., and holding time of 1h-3h.

[0069] The high temperature sintering temperature of the wax removal in step S51 is 700°C-900°C, and the sintering time is 1h-3h. For example, the sintering temperature may be, but is not limited to, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 840°C, 860°C, 880°C, 900°C, or a range consisting of any two of these values. Optionally, the sintering time may be, but is not limited to, 1h, 1.5h, 2h, 2.5h, 3h, or a range consisting of any two of these values.

[0070] like Figure 1As shown in the figure, when expanding at high temperature, both too low and too high expansion temperatures will affect the final expansion effect of expandable graphite. The optimal expansion temperature of expandable graphite is 900℃. When the expansion temperature is lower than 700℃, the expansion volume does not change significantly with temperature. Because the expansion temperature is low, on the one hand, the expansion is incomplete, and the interlayer spacing of graphite cannot reach the optimal state. On the other hand, the decomposition rate of the interlayer compound is too low, the decomposition is incomplete, the push generated is small, and the graphite interlayer spacing is not opened much, so the graphite expansion volume is very small. After 700℃, the decomposition rate of the graphite interlayer compound increases sharply with the increase of the expansion temperature; the expansion volume of graphite also gradually increases. When the expansion temperature is higher than 900℃, the expansion volume of graphite is too large, which can easily lead to defects such as tiny cracks in the matrix and excessive porosity, and poor matrix reliability.

[0071] The preparation method of the porous ceramic is simple and easy to process, and can realize the integrated molding and sintering of the porous ceramic atomizer core and the oil guide tube. The ceramic body has small shrinkage and can form a close fit with the oil guide tube, thereby reducing the risk of leakage and improving the production efficiency and product stability of the atomizer core.

[0072] The present invention also provides a porous ceramic atomization core, which is prepared according to the above-mentioned method for preparing a porous ceramic, and has a shrinkage rate of -0.10-0.05%, a porosity of 50-60%, and a thermal conductivity of 2.0W / (m·K)-3.0W / (m·K). For example, in some embodiments, the porosity of the porous ceramic atomization core can be 50%, 52%, 55%, 57%, 58%, 59%, 60% or can be a range consisting of any two of the above values, for example, 50.1%-55.2% or 52.2%-54.3%; the thermal conductivity of the porous ceramic atomization core can be 2.05W / (m·K), 2.25W / (m·K), 2.50W / (m·K), 2.75W / (m·K), 3.00W / (m·K) or can be a range consisting of any two of the above values, for example, 2.55W / (m·K)-2.65W / (m·K).

[0073] The present invention further provides an electronic atomization device, comprising the above-mentioned porous ceramic atomization core. It is understandable that the electronic atomization device may also include other components commonly used in the art, which will not be described in detail here.

[0074] The following is a detailed description in conjunction with specific examples. The following examples do not include other components except for inevitable impurities unless otherwise specified. The reagents and instruments used in the examples are conventionally selected in the art unless otherwise specified. The experimental methods for which specific conditions are not specified in the examples are implemented according to conventional conditions, such as the conditions described in the literature, books, or the methods recommended by the manufacturer. Unless otherwise specified, the parts in the following examples and comparative examples are all by weight.

[0075] Example 1

[0076] A porous ceramic, wherein the ceramic raw material comprises inorganic powder and organic components, wherein the weight ratio of the inorganic powder to the organic components is 100:28.

[0077] Specifically, the inorganic powder includes, by weight: 5 parts of diatomaceous earth, 50 parts of aluminum nitride, 10 parts of mullite, 10 parts of low-melting-point glass powder, 10 parts of PS microspheres, 5 parts of wollastonite, and 10 parts of expandable graphite; the organic components include, by weight: 20 parts of paraffin, 5 parts of stearic acid, and 3 parts of beeswax.

[0078] In this embodiment, a method for preparing a porous ceramic includes:

[0079] S1. Mixing ingredients: weigh ceramic raw materials according to the above formula to obtain an inorganic powder mixture and an organic component mixture;

[0080] S2, mixing and drying: placing the inorganic powder mixture into a three-dimensional mixer for mixing for 2 hours, and drying at 60° C. for 12 hours;

[0081] S3, preparing wax slurry: placing the organic component mixture of step S1 into a wax machine and heating it at 100° C. to melt; then adding the dried inorganic powder mixture of step S2 and stirring evenly to obtain wax slurry;

[0082] S4, die-casting: placing the wax slurry in step S3 into a mold containing an oil guide pipe and a heating component for die-casting to obtain a porous ceramic body;

[0083] S50, pre-sintering of the body: placing the porous ceramic body in an air furnace for pre-sintering to remove wax from the porous ceramic body, the pre-sintering temperature is 200° C., and the holding time is 3 hours;

[0084] S51, placing the pre-fired porous ceramic body in a vacuum sintering furnace for sintering to obtain a porous ceramic atomization core, with a vacuum degree below 0.01 Pa, a sintering temperature of 900° C., and a heat preservation time of 1 hour.

[0085] Example 2

[0086] A porous ceramic, wherein the ceramic raw material comprises inorganic powder and organic components, wherein the weight ratio of the inorganic powder to the organic components is 100:28.

[0087] Specifically, the inorganic powder, measured by weight, includes: 5 parts of attapulgite, 40 parts of silicon nitride, 15 parts of mullite, 10 parts of low-melting-point glass powder, 15 parts of starch, 10 parts of diopside, and 5 parts of expandable graphite; the organic components, measured by weight, include: 20 parts of paraffin, 3 parts of stearic acid, and 5 parts of beeswax.

[0088] In this embodiment, a method for preparing a porous ceramic includes:

[0089] S1. Mixing ingredients: weigh ceramic raw materials according to the above formula to obtain an inorganic powder mixture and an organic component mixture;

[0090] S2, mixing and drying: placing the inorganic powder mixture into a three-dimensional mixer for mixing for 2 hours, and drying at 60° C. for 12 hours;

[0091] S3, preparing wax slurry: placing the organic component mixture of step S1 into a wax machine and heating it at 100° C. to melt; then adding the dried inorganic powder mixture of step S2 and stirring evenly to obtain wax slurry;

[0092] S4, die casting: placing the wax slurry in step S3 into a mold containing an oil guide tube and a heating component for die casting, the temperature is controlled at 200° C., the pressure is 0.6 MPa, the pressure holding time is 5 s, and the porous ceramic body is obtained by die casting;

[0093] S50, pre-sintering of the body: placing the porous ceramic body in an air furnace for pre-sintering to remove wax from the porous ceramic body, the pre-sintering temperature is 200° C., and the holding time is 3 hours;

[0094] S51, placing the pre-fired porous ceramic body in a vacuum sintering furnace for sintering to obtain a porous ceramic atomization core, with a vacuum degree below 0.01 Pa, a sintering temperature of 850° C., and a heat preservation time of 2 h.

[0095] Example 3

[0096] A porous ceramic, wherein the ceramic raw material comprises inorganic powder and organic components, wherein the weight ratio of the inorganic powder to the organic components is 100:33.

[0097] Specifically, the inorganic powder, measured by weight, includes: 10 parts of diatomaceous earth, 30 parts of aluminum nitride, 20 parts of mullite, 15 parts of low-melting-point glass powder, 5 parts of sucrose, 10 parts of wollastonite, and 10 parts of expandable graphite; the organic components, measured by weight, include: 25 parts of paraffin, 5 parts of stearic acid, and 3 parts of beeswax.

[0098] In this embodiment, a method for preparing a porous ceramic includes:

[0099] S1. Mixing ingredients: weigh ceramic raw materials according to the above formula to obtain an inorganic powder mixture and an organic component mixture;

[0100] S2, mixing and drying: placing the inorganic powder mixture into a three-dimensional mixer for mixing for 2 hours, and drying at 60° C. for 12 hours;

[0101] S3, preparing wax slurry: placing the organic component mixture of step S1 into a wax machine and heating it at 100° C. to melt; then adding the dried inorganic powder mixture of step S2 and stirring evenly to obtain wax slurry;

[0102] S4, die-casting: placing the wax slurry in step S3 into a mold containing an oil guide pipe and a heating component for die-casting to obtain a porous ceramic body;

[0103] S50, pre-sintering of the body: placing the porous ceramic body in an air furnace for pre-sintering to remove wax from the porous ceramic body, the pre-sintering temperature is 200° C., and the holding time is 3 hours;

[0104] S51, placing the pre-fired porous ceramic body in a vacuum sintering furnace for sintering to obtain a porous ceramic atomization core, with a vacuum degree below 0.01 Pa, a sintering temperature of 750° C., and a heat preservation time of 2 h.

[0105] Example 4

[0106] A porous ceramic, wherein the ceramic raw material comprises inorganic powder and organic components, wherein the weight ratio of the inorganic powder to the organic components is 100:38.

[0107] Specifically, the inorganic powder, measured by weight, includes: 15 parts of attapulgite, 20 parts of silicon nitride, 30 parts of mullite, 20 parts of low-melting-point glass powder, 5 parts of wood powder, 5 parts of diopside, and 5 parts of expandable graphite; the organic components, measured by weight, include: 28 parts of paraffin, 3 parts of stearic acid, and 7 parts of beeswax.

[0108] In this embodiment, a method for preparing a porous ceramic includes:

[0109] S1. Mixing ingredients: weigh ceramic raw materials according to the above formula to obtain an inorganic powder mixture and an organic component mixture;

[0110] S2, mixing and drying: placing the inorganic powder mixture into a three-dimensional mixer for mixing for 2 hours, and drying at 60° C. for 12 hours;

[0111] S3, preparing wax slurry: placing the organic component mixture of step S1 into a wax machine and heating it at 100° C. to melt; then adding the dried inorganic powder mixture of step S2 and stirring evenly to obtain wax slurry;

[0112] S4, die-casting: placing the wax slurry in step S3 into a mold containing an oil guide pipe and a heating component for die-casting to obtain a porous ceramic body;

[0113] S50, pre-sintering of the body: placing the porous ceramic body in an air furnace for pre-sintering to remove wax from the porous ceramic body, the pre-sintering temperature is 200° C., and the holding time is 3 hours;

[0114] S51, placing the pre-fired porous ceramic body in a vacuum sintering furnace for sintering to obtain a porous ceramic atomization core, with a vacuum degree below 0.01 Pa, a sintering temperature of 700° C., and a heat preservation time of 3 h.

[0115] Comparative Example 1

[0116] The difference between Comparative Example 1 and Implementation 1 is that expandable graphite and wollastonite are not added, and the amount of mullite is increased from 10 parts to 25 parts.

[0117] Comparative Example 2

[0118] The difference between Comparative Example 2 and Implementation 1 is that expandable graphite is not added, and the amount of mullite powder is increased from 10 parts to 20 parts.

[0119] Comparative Example 3

[0120] The difference between Comparative Example 3 and Implementation 1 is that expandable graphite is not added, and 70 parts of quartz powder are used to replace aluminum nitride and mullite.

[0121] Comparative Example 4

[0122] The difference between Comparative Example 4 and Implementation 1 is that 55 parts of quartz powder are used to replace aluminum nitride and mullite, and the content of expandable graphite is increased to 15 parts.

[0123] Table 1 Ingredients of Examples 1-4 and Comparative Examples 1-4

[0124]

[0125]

[0126] The porous ceramic atomizer cores prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to performance tests, and the test data were integrated, as shown in Table 2 below.

[0127] Table 2 Performance test data of porous ceramic atomizer core

[0128] \ Porosity % Shrinkage % Thermal conductivity % Example 1 56.3 -0.53 2.86 Example 2 55.9 -0.36 2.43 Example 3 54.3 -0.14 2.16 Example 4 50.3 0.06 2.01 Comparative Example 1 53.6 3.9 1.56 Comparative Example 2 54.6 1.86 1.49 Comparative Example 3 55.2 1.79 0.58 Comparative Example 4 68.3 -0.89 1.03

[0129] With reference to Table 1 and Table 2, in Examples 1-4, the weight ratio of the inorganic powder and the organic component is reasonably controlled, the inorganic powder is selected from a reasonable amount of the first base material, the second base material, the third base material, the binder, the pore former and the sintering aid, and supplemented with a reasonable amount of expandable graphite, and the organic component is selected from a reasonable amount of plasticizer and surfactant, so that a porous ceramic atomization core with low shrinkage, moderate porosity and high thermal conductivity can be prepared.

[0130] Among them, the first base material includes diatomaceous earth, one or two of attapulgite; diatomaceous earth, one or two of attapulgite are added to the ceramic raw materials as aggregates to improve the adsorption performance of the porous ceramic, which can ensure the mechanical strength of the porous ceramic atomization core after wax removal and sintering, and at the same time improve the liquid locking ability of the porous ceramic atomization core and reduce the risk of leakage.

[0131] The second base material includes one or two of silicon nitride and aluminum nitride. Compared with silicon dioxide, silicon nitride and aluminum nitride have the characteristics of high thermal conductivity and high strength. Selecting a reasonable amount can improve the thermal conductivity of the porous ceramic atomizer core while further improving the mechanical strength of the porous ceramic atomizer core.

[0132] The third base material includes mullite powder, which provides a higher strength of the skeleton after sintering and improves the thermal conductivity to a certain extent.

[0133] The sintering aid is one or both of wollastonite and diopside. Wollastonite and diopside reduce the sintering temperature of the green body during the sintering process and both do not contain organic matter and structural water. The drying and sintering shrinkage is very small, which can reduce the overall sintering shrinkage of the ceramic to a certain extent.

[0134] As a filler, expandable graphite is a layered material made from fine flake graphite through intercalation modification. Its volume can expand rapidly during high-position sintering, which can resist the shrinkage of the ceramic matrix and promote the close fit between the porous ceramic and the oil guide tube.

[0135] The plasticizer is paraffin in a reasonable amount to make the porous ceramic body more plastic; the surfactant is beeswax and / or stearic acid in a reasonable amount to improve the solubility of organic components, making it easier to mix the ceramic raw materials evenly.

[0136] The porous ceramic atomizer core obtained by drying the above-mentioned mixture, preparing wax slurry, hot-die casting, and dewaxing and sintering has the characteristics of high mechanical strength, moderate porosity, and high thermal conductivity. When the porous ceramic atomizer core atomizes the aerosol generating matrix, it can be fully preheated and has a high liquid conduction rate, so that an electronic atomization device with good stability and high delicate taste can be obtained, which makes the electronic atomization device more consistent and the user experience higher.

[0137] In Comparative Example 1, expandable graphite and wollastonite were not added, mullite was increased from 10 parts to 25 parts, and other ingredients were the same as those in Example 1. Referring to Table 2, since expandable graphite and wollastonite were removed from Comparative Example 1, the volume shrinkage of the porous ceramic atomization core was large.

[0138] In Comparative Example 2, only expandable graphite is not added, mullite powder is increased from 10 parts to 20 parts, and other ingredients are the same as those in Example 1. Referring to Table 2, since Comparative Example 2 removes expandable graphite and retains wollastonite, the volume shrinkage rate of the porous ceramic atomization core is significantly greater than that of the embodiment and less than that of Comparative Example 1.

[0139] In comparative example 3, expandable graphite was not added, and 70 parts of quartz powder were used to replace aluminum nitride and mullite. Referring to Table 2, compared with example 1, the thermal conductivity of the porous ceramic atomization core decreased significantly and the shrinkage rate increased significantly.

[0140] In Comparative Example 4, 55 parts of quartz powder are used to replace aluminum nitride and mullite, and the content of expandable graphite is increased to 15 parts. Referring to Table 2, compared with Example 1, the thermal conductivity of the porous ceramic atomization core decreases significantly and the porosity increases significantly.

[0141] Combining Examples 1-4 and Comparative Examples 1-4, it can be seen that aluminum nitride and silicon nitride are beneficial to improving the thermal conductivity of the porous ceramic atomizer core, and wollastonite and diopside are beneficial to reducing the shrinkage rate of the porous ceramic atomizer core to a certain extent. Expandable graphite plays an important role in controlling the shrinkage rate of porous ceramics. By reasonably selecting the amount of each material, a porous ceramic atomizer core with low shrinkage, moderate porosity and high thermal conductivity can be prepared.

[0142] The above contents are further detailed descriptions of the present invention in combination with specific / preferred implementations, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, they can also make several substitutions or modifications to these described embodiments without departing from the concept of the present invention, and these substitutions or modifications should be regarded as belonging to the protection scope of the present invention.

Claims

1. A porous ceramic, characterized in that: Made of ceramic raw materials, the ceramic raw materials include inorganic powder and organic components, the inorganic powder includes 35-80 parts of ceramic aggregate, 5-30 parts of binder, 5-20 parts of pore former, 3-15 parts of sintering aid and 3-12 parts of expandable graphite by weight; The organic components include 15-35 parts of plasticizer and 1-10 parts of surfactant by weight.

2. A porous ceramic according to claim 1, characterized in that: The ceramic aggregate comprises 5-20 parts of a first base material, 15-60 parts of a second base material and 5-35 parts of a third base material; The first base material includes one or two of diatomaceous earth and attapulgite; The second base material includes one or both of silicon nitride and aluminum nitride; The third base material includes mullite powder.

3. A porous ceramic according to claim 2, characterized in that: The sintering aid is one or two of wollastonite and diopside.

4. A porous ceramic according to claim 2, characterized in that: The pore-forming agent includes one or more of sucrose, polystyrene microspheres, wood powder, phenolic resin powder, epoxy resin powder, and starch; and / or, the plasticizer comprises paraffin; And / or, the surfactant includes one or both of beeswax and stearic acid.

5. The porous ceramic according to claim 2, characterized in that: The inorganic powder comprises, by weight, 5-15 parts of the first base material, 20-50 parts of the second base material, 10-30 parts of the third base material, 10-20 parts of the binder, 5-15 parts of the pore former, 5-10 parts of the sintering aid, and 5-10 parts of the expandable graphite. The weight ratio of the inorganic powder to the organic component is 100:28-100:

38.

6. A method for preparing porous ceramics, characterized in that: The following steps are involved: S1. Ingredients: According to the formula, ceramic aggregate, binder, pore former, sintering aid, expandable graphite, plasticizer and surfactant are weighed to obtain an inorganic powder mixture and an organic component mixture respectively; S2, mixing and drying: mixing the inorganic powder mixture in step S1 uniformly and drying to remove moisture; S3, preparing wax slurry: heating and melting the organic component mixture in step S1, and then adding the inorganic powder mixture in step S2 and stirring evenly to obtain wax slurry; S4, die casting: placing the wax slurry in step S3 into a mold containing an oil guide tube and a heating component for hot die casting, so that the porous ceramic blank is integrally formed with the oil guide tube and the heating component, and the inner side wall and the outer peripheral side of the porous ceramic blank are respectively in contact with the heating component and the oil guide tube; S5, dewaxing and sintering: Dewaxing and sintering the porous ceramic body in step S4 to obtain a porous ceramic atomizing core.

7. The method for preparing a porous ceramic according to claim 6, characterized in that: Step S5 wax removal and sintering includes: S50, pre-sintering the body: placing the porous ceramic body in an air furnace for pre-sintering to remove wax from the porous ceramic body; S51, sintering the porous ceramic atomizer core: placing the pre-fired porous ceramic green body in a vacuum sintering furnace for sintering to obtain a porous ceramic atomizer core.

8. The method for preparing a porous ceramic according to claim 6, characterized in that: Before step S1, the process further includes preparing the expandable graphite: Take graphite, use a strong oxidant to perform intercalation modification under strong acid conditions, wash with water until the pH value is weakly acidic, and bake and dry to obtain expandable graphite.

9. A porous ceramic atomizing core obtained by the preparation method according to claim 8, characterized in that: The porous ceramic has a porosity of 50-60%, a shrinkage of -0.10-0.05%, and a thermal conductivity of 2.0 W / (m·K)%-3.0 W / (m·K).

10. An electronic atomization device, characterized in that: Comprising the porous ceramic atomization core as described in claim 9.

Citation Information

Patent Citations

  • Expandable magnesium carbon fire clay as well as preparation method and application thereof

    CN114315391A

  • Porous ceramic, preparation method thereof, atomizing core and electronic atomizing device

    CN117602960A